The Importance of Rhythmic Stimulation for Preterm Infants in the NICU - Joëlle Provasi; Loreline Blanc; Isabelle Carchon (MDPI AG, 2021)
The fetal environment provides the fetus with multiple potential sources of rhythmic stimulation that are not present in the NICU. Maternal breathing, heartbeats, walking, dancing, running, speaking, singing, etc., all bathe the fetus in an environment of varied rhythmic stimuli: vestibular, somatosensory, tactile, and auditory. In contrast, the NICU environment does not offer the same proportion of rhythmic stimulation. After analyzing the lack of rhythmic stimulation in the NICU, this review highlights the different proposals for vestibular and/or auditory rhythmic stimulation offered to preterm infants alone and with their parents. The focus is on the beneficial effects of auditory and vestibular stimulation involving both partners of the mother-infant dyad. A preliminary study on the influence of a skin-to-skin lullaby on the stability of maternal behavior and on the tonic emotional manifestations of the preterm infant is presented as an example. The review concludes with the importance of introducing rhythmic stimulations in the NICU.